Phytophthora genus fungal influence on the spruce seedlings’s root system dying off - Kramarets, Volodymyr; Matsiakh , Iryna (Forestry, Forest, Paper and Woodworking Industry, 2024)
Laboratory research showed the results of the influence of the fungal pathogen of the Phytophthora genus such as Ph. cinnamomi, Ph. citrophthora, Ph. cactorum, Ph. ramorum, Ph. alni, Ph. gonapodides, Ph. cambivora on the dying off of the one-year spruce seedlings’s root system. All the types of the Phytophora genus presented in the study showed high pathogenicity for the roots – more than 92 % of the root system died off in 8 days. The most intensive influence on the roots and their dying off had Ph.citrophthora, the slightest influence had Ph. cambivora and Ph. gonapodides. Authenticity of the survey results is confirmed by using tests like Dunetta and post-hoc Tukey calculated with the help of Statistika 9 Programme.